Deber de reparación integral y femicidio en Ecuador: análisis de la respuesta estatal (2014-2021) [Sección Abierta] - Carvalho, Marcella Da Fonte (2025)
The duty of due diligence, as a state obligation under human hights law, encompasses the key categories of prevention, investigation, punishment, and reparation. Among these, reparation holds particular significance as a fundamental right for femicide victims. This article delineates the international obligation of due diligence and the duty to provide reparation, framing them as critical pillars for ensuring access to justice. The study aimed to assess the effectiveness of comprehensive reparation within the Ecuadorian justice system’s response to femicide victims, employing a gender and intersectionality approach. Findings reveal that ineffective investigations result in numerous cases without convictions and limited recognition of indirect victims. In cases where convictions were secured, compensation was the predominant remedy, with other forms of reparation largely neglected. The number of cases mandating comprehensive reparation is exceptionally low, and reparations varied based on the direct victim’s categorization, underscoring systemic asymmetries in access to justice.